BIBLIOTECARUL – ELEMENTUL CREATOR, IMPLICAT ŞI COORDONATOR AL ACTIVITĂŢII BIBLIOTECII - IFTODI, director, Biblioteca „L. Rebreanu”, Lina (BIBLIOPOLIS, 2020)
Librarians are one of the most important investment of a library, because they have the potential to create valuable products and services that meet new requirements or can respond better to the old requirements. In the article the author aims to present the efficiency of librarians’ creativity and its influence on current and future development of libraries and information services, being an innovation factor in achieving their performance. It also contains some opinions on this subject of the researchers and some innovative ideas generated and implemented by librarians of the Library "Rebreanu". Certainly libraries need creative librarians for success, for their competitiveness - concluded the article. The libraries progress depends on the professionalism, flexibility and level of creativity of librarians. New ideas do not just require a launch, but the implementation for library and community benefit. Such libraries can gain users' trust and prosper in this world of variation, difference and diversity.